Variations of heat transfer mechanism and flow structure in a heat exchanger tube fitted with 30 inclined ring - Amnart Boonloi; Withada Jedsadaratanachai (My University, 2020)
Flow prediction, heat transfer pattern, and thermo-hydraulic efficiency in a heat exchanger tube fitted with vortex generator are chosen for the present research. The 30° inclined ring is opted to develop the performance of the heat exchanger tube. The effects of inclined ring configuration and placement in the heat exchanger tube on the patterns of flow and heat transfer are investigated. The Reynolds number (at the entry zone of the periodic model) in the range of around 100–2000 (laminar flow region) is discussed. The heat transfer ability, pressure loss, and efficiency of the heat exchanger tube fitted with 30° inclined ring are analyzed with the numerical method (finite volume method). The SIMPLE algorithm of the commercial code is picked for the present study. The simulated results in the heat exchanger tube fitted with 30° inclined ring are offered in patterns of streamlines, temperature contour, and Nusselt number contour. From the preliminary result, it is found that the creation model of the heat exchanger tube fitted with 30° inclined ring has sufficient reliance to measure flow and heat transfer profiles. The installment of the 30° inclined ring in the heat exchanger tube leads to greater heat transfer ability and thermo-hydraulic performance because of the creation of the vortex flow and thermal boundary layer disturbance on the heat exchanger tube surface. The heat transfer ability in the heat exchanger tube fitted with 30° inclined ring is found to be around 1.00–10.56 times above the plain circular tube. In addition, the installation of the 30° inclined ring in the heat exchanger tube gives the maximum thermal enhancement factor around 3.18.
Keywords: Heat Transfer Mechanisms